(untitled) (Medical Forum Monthly, 2020)
Objective: The objective of this study is to know the frequency of choledocholithiasis, biliary stricture and carcinoma head of pancreas among patients having obstructive jaundice. Study Design: Cross-sectional, descriptive study Place and Duration of Study: This study was conducted at the Department of Gastroenterology, four Medical units and four Surgical units at Bahawal Victoria Hospital Bahawalpur from January 2019 to June 2019. Materials and Methods: A total of 201 patients diagnosed as obstructive jaundice with serum bilirubin level of greater than 3 mg/dl were included. The Intra and Extra hepatic biliary channels, presence of gall stones, common bile duct and any abdominal mass were seen by ultrasonography abdomen. Endoscopic retrograde cholangiopancreatography also done in patients with obstructive jaundice. Data regarding choledocholithiasis, carcinoma head of pancreas and biliary stricture was collected. Results: This study included age range from 40 to 70 years with mean age of 52.24 ± 5.34 years. Majority of the patients were between 51 to 60 years age groups i.e. 57.8%. Majority of patients were females (62.7%). Mean weight was 78.78 ± 12.52 Kg and mean BMI was 26.293±2.87 kg/m2. The frequency of choledocholithiasis was 33.3%, carcinoma of head of pancreas 30.8% and biliary stricture was 7%. Conclusion: The results concluded that Choledocholithiasis is the commonest benign etiology among patients with obstructive jaundice. It is more prevalent in females. This study shows that early diagnosis and intervention has significant role for the prognosis of patients with obstructive jaundice.